Constructing, Deconstructing or Abolishing? Discourses on Masculinities in Violence Against Women Prevention by Stakeholders in Spain - Nardini, Krizia (Journal of interpersonal violence, 2025)
In the field of violence against women (VAW) prevention, one of the current questions at stake is how to address men’s role and masculinities, but it is still an emerging field in Spain. The aim of this study was to analyze the up-to-date discourses on masculinity among stakeholders in the field of VAW prevention and gender equity in Spain. We used a qualitative methodology with semi-structured interviews, conducted between October 2019 and February 2020 in Madrid and Alicante (Spain), with 23 key stakeholders from different areas: in governmental (public health and VAW prevention/intervention, and institutional and policy positioning) and nongovernmental organizations (anti-violence masculinities workers, youth education workers, and feminist and LGBT associations). A discourse analysis was performed with the data collected. Our findings showed that discourses around masculinities among Spanish stakeholders in VAW prevention and gender equity were diverse and presented different layers of critique. Despite a general agreement on the importance of transforming sexist men’s practices toward more gender equitable relations, three main interpretive repertoires were identified: “Constructing positive/new masculinities” discourse, focused on promoting men’s engagement and egalitarian practices; “Deconstructing hegemonic masculinity” discourse, intended to critically identify and question harmful masculinities norms; and “Abolishing gender” discourse, which aims at dismantling masculinity, and gender in general, as a social structure that generates oppression in itself, advocating for its abolition. Those interpretive repertoires were not mutually exclusive and sometimes stakeholders incorporate in their work more than one approach. The study findings shed light on this current emerging and urgent debate and contributes more broadly to the critical assessment of the concepts used and their implications for VAW prevention.